The Bélinga Iron Ore Deposit ( 2.8 Ga), NE-Gabon: Reactualization and New Interpretations on Crests - Kondja, Stévy Retonda; Ondo, Simplice Marin Ndong; Minko, Ambroise Edou; Mikolo, Francis Mayaga (European Scientific Journal, ESJ, 2017)
The Bélinga iron ore deposit is the biggest iron ore situated in NEGabon. Very little is known about that iron ore and available data are sometimes incompatible. We revisited documents that evoke the deposit to reactualize and propose new interpretations. The Bélinga iron ore deposit is composed of thirteen (13) N-S mineralized crests that underwent 3 tectonic events, folding (D1), fracture (D2) and folding (D3). The ore is subdivided into four main categories which are blue and yellow ores, hematitic phyllites and enriched itabirites, with variable amounts of canga. The estimated reserves at Bélinga are 384 Mt of high grade ore (Fe > 60% and P < 0.09%), and more than 1 Gt by considering an iron ore with Fe > 50% and P < 0.18%.